Behind closed doors: The delivery of performance analysis in a professional New Zealand rugby club - Middlemas, S.; Croft, H. (World Congress of Performance Analysis of Sport XI - Alicante, 16th - 18th November 2016, 2016)
Video ab 4:11:23